Limitations of Public Interest Clause in Land Acquisition So That Land Rights Holders Can Retain Their Rights - Rias Frihandini (NORMA, 2021)
This research aims to see and analyze legal protection for land rights holders who lost their land rights due to public interest clause, whether for the benefit of the state or the private sector. Based on the 1945 Constitution, it can be seen that the use of the earth (land), water, and natural resources contained therein by the state is required to be used for the greatest prosperity of the people, and not for certain elites from government agencies who need land. Limitations must be applied to this clause so that the use is not arbitrary because even though the land rights are ownership rights, it can lose since the Government carries it out. The public interest clause is always the way and the Government answer for those who refuse their land to be acquired. Research results are that public interests, which are the needs of many people or broad goals, must pay attention to social, political, psychological, vindication and security aspects based on the National development principle.Keywords: Land, Public Interest, Acquisition